Prevalence of Bone Mineral Disorder in Hemodialysis patients: A Single Centered Study of Local Population - Azhar Nasim, Zahid Rafique, Ali Talal, Aurangzeb Afzal, Asmara Asrar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mineral homeostasis deteriorates when kidney function diminishes, manifesting as variations in blood and tissue levels of calcium and phosphate, followed by the change in circulating parathyroid hormone (PTH). Mineral bone disorders (MBD) are a clinical illness caused by chronic renal disease that expresses as a systemic impairment of mineral and bone metabolism. Aim: To find out prevalence of bone mineral disorders in hemodialysis patients presenting in Nephrology Ward, SIMS. Lahore Methodology: This observational analysis included a total of 88 patients, who were on dialysis at the nephrology department of SHL for the period of more than six months. The study was conducted from 17 September 2021 to 10 March 2022 after the approval of the ethical review board of the Department. According to their blood PTH levels, the patients were split into three groups: those with PTH levels less than 150 pg/ml (low bone turnover), those with PTH levels between 150 and 300 pg/ml (normal bone turnover), and those with PTH levels greater than 300 pg/ml (high bone turnover). Results: The prevalence of bone mineral disorder was 87.5% in hemodialysis patients presenting at the nephrology department, in which prevalence of high turnover bone disorder was 73.9% whereas the prevalence of low turnover bone disorder was 13.6%. In the early dialysis period (0.5-5 years) the prevalence of bone mineral disorders was more prominent as compared to the patients on dialysis for more than 5 years. Conclusion: There was a high prevalence of bone mineral disorders, in which patients with high turnover were found to be more prevalent. Similarly, patients in the early years of dialysis are more prone to develop bone mineral disorders. Thus, we should keep these findings in mind while doing the follow up and adjust the medication accordingly.